2018
DOI: 10.1101/242933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential regulation of microRNA-15a by radiation affects angiogenesis and tumor growth via modulation of acid sphingomyelinase

Abstract: Activation of acid sphingomyelinase (SMPD1) and the generation of ceramide is a critical regulator of apoptosis in response to cellular stress including radiation. Endothelial SMPD1 has been shown to regulate tumor responses to radiation therapy. We show here that the SMPD1 gene is regulated by a microRNA (miR), miR-15a, in endothelial cells (ECs). Standard low dose radiation (2 Gy) upregulates miR-15a and decreases SMPD1 levels. In contrast, high dose radiation (10 Gy and above) decreases miR-15a and increase… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The mouse model of colorectal cancer found that inhibiting miR-15a increased the expression of SMPD1, promoted rapid apoptosis of endothelial cells, and inhibited tumor growth. An analysis of 182 patients with CRC showed that patients with low SMPD1 [19] expression were associated with poor prognosis. Lin et al [20] found that SMPD2 expression in exosomes inhibited HCC growth by decreasing the sphingomyelin/ceramide ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse model of colorectal cancer found that inhibiting miR-15a increased the expression of SMPD1, promoted rapid apoptosis of endothelial cells, and inhibited tumor growth. An analysis of 182 patients with CRC showed that patients with low SMPD1 [19] expression were associated with poor prognosis. Lin et al [20] found that SMPD2 expression in exosomes inhibited HCC growth by decreasing the sphingomyelin/ceramide ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Rb overexpression has also been shown to reverse radiation resistance induced by miR-622 in vitro. [37] The results reported by Rana et al [38] suggest that the activation of acid sphingolipids (sphingomyelin phosphodiesterase 1, SMPD1) and the production of ceramides are key processes in the regulation of apoptosis in response to cellular stress, including radiation. Low expression levels of miR-15a upregulate SMPD1 levels, inducing apoptosis and increasing radiosensitivity.…”
Section: Mirnas Affect the Response To Rc Radiotherapy By Regulating ...mentioning
confidence: 99%